Anti corruption mechanisms and public finance management efficiency in Ukraine’s war and post-war recovery - Moisiiakha, Andrii; Velychko, Kateryna; Kovalenko, Nataliia; Zhurba, Oleksandr; Kramar, Oleh (The Economics and Finance Letters, 2025)
This report analyzes the potential contribution of anti-corruption measures to improving Public Financial Management as part of Ukraine’s anticipated post-war reconstruction. It draws on several comparative case studies from countries that have emerged from conflict, including Croatia, Georgia, Hungary, Bosnia and Herzegovina, and Rwanda. Although Ukraine remains in a state of war, this article adopts a forward-looking perspective and applies insights from post-conflict economies to explore possible policy implications. The primary objective is to highlight the role of anti-corruption efforts, institutional reform, and transparency in enhancing fiscal governance within fragile contexts. The study employs a panel dataset covering six conflict-affected economies for the period 2020-2025. It applies econometric methods, including cross-sectional dependence tests, CADF and CIPS unit root analysis, Fixed Effects estimation, and Two-Stage Least Squares (2SLS) estimation, to examine the relationships between governance reforms and PFM outcomes. Results show that anti-corruption measures, such as the establishment of independent agencies and the implementation of e-procurement systems, contribute positively to fiscal transparency and budget discipline. Institutional soundness, along with the supportive role of foreign aid and international institutions, also emerges as a significant factor. There are precise policy insights for Ukraine. The study offers a meaningful forward-looking roadmap, grounded in empirical evidence from comparable post-conflict countries, outlining effective strategies for achieving sound public financial management during the reconstruction period.